Effect of microbiologically enriched fertilizers on soil microorganisms in the rhizosphere of apple trees - Lidia Sas Paszt; Urszula Smolińska; Paweł Trzciński; Augustyn Mika; Sławomir Głuszek; Edyta Derkowska; Anna Lisek; Krzysztof Górnik; Beata Sumorok; Magdalena Szczech; Beata Kowalska; Waldemar Treder (Horticultural Science, 2023)
In long-term cultivation of apple trees, replantation disease may occur, caused by a set of biotic and abiotic factors, occurring in the soil, e.g. the accumulation of pathogenic and harmful microorganisms. Beneficial microorganisms can be of great importance in limiting orchard replant disease. In our study, the Urea fertilizer was enriched with Aspergillus niger and Purpureocillium lilacinum fungi, while the Polifoska 6 and Super Fos Dar 40 fertilizers with strains of the bacteria Bacillus spp., Bacillus amyloliquefaciens, and Paenibacillus polymyxa. The aim of the three-year study was to determine what effects the application of mineral fertilizers enriched with beneficial microorganisms, applied in 100% doses and in doses lower by 40% had on the microorganisms in the rhizosphere of apple trees. The number of bacteria of the genus Pseudomonas in the rhizosphere of apple trees was the highest in the combination with Urea 60% + fungi and Polifoska 60% + bacteria. These values were 2-3 times higher compared with the control. In the combination with Polifoska 60% + bacteria, the number of fluorescent Pseudomonas bacteria was five times higher compared to the control. The highest number of actinomycetes was observed in the third year of the study, in the combination with Polifoska 60% + bacteria. The use of this fertilizer increased the number of these bacteria more than five-fold compared with the control. The beneficial effect of Polifoska 60% + bacteria, Super Fos Dar 100% + bacteria, and Urea 60% + fungi on phosphate-solubilizing bacteria was observed in the third year of cultivation. The additional application of filamentous fungi together with Urea did not have a significant effect on this group of microorganisms. The obtained results show that in many cases the application of the selected fertilizers positively influenced the microorganisms inhabiting the apple-tree rhizosphere. Particularly noteworthy is Polifoska enriched with the selected bacteria, the use of which significantly increased the number of beneficial bacteria of the genus Pseudomonas.